2022
DOI: 10.1007/s12026-022-09347-z
|View full text |Cite
|
Sign up to set email alerts
|

ANA-specific antibodies, ANA patterns, anti-ds-DNA results, and clinical diagnosis: a laboratory and clinical audit

Abstract: Background: The diagnosis of systemic autoimmune diseases (SAID) is challenging, due to overlapping features with other non-immune disorders. Antinuclear antibodies (ANA) /anti-cellular antibodies are the sensitive screening tests but anti-double-stranded-deoxyribonucleic acid-antibody (anti-ds-DNA), and ANA-speci c antibodies are speci c for SAID. We aimed to look at ANA-speci c antibodies in our patients and correlated them with ANA patterns, anti-ds-DNA, and clinical diagnosis for proper interpretation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The deposition of various autoantibodies plays a key role in the onset, progression, and severity of LN and is of great value in its diagnosis, treatment, and prognosis ( Oelzner et al, 2003 ; van der Vlag and Berden, 2011 ). Anti-ds-DNA and ANA-specific antibodies are specific to systemic autoimmune diseases ( Anis et al, 2023 ), and ds-DNA-Ab was significantly positively correlated with c_Bacteria_unclassified in our study. SLEDAI is a commonly used disease activity scoring tool in clinical practice.…”
Section: Discussionsupporting
confidence: 59%
“…The deposition of various autoantibodies plays a key role in the onset, progression, and severity of LN and is of great value in its diagnosis, treatment, and prognosis ( Oelzner et al, 2003 ; van der Vlag and Berden, 2011 ). Anti-ds-DNA and ANA-specific antibodies are specific to systemic autoimmune diseases ( Anis et al, 2023 ), and ds-DNA-Ab was significantly positively correlated with c_Bacteria_unclassified in our study. SLEDAI is a commonly used disease activity scoring tool in clinical practice.…”
Section: Discussionsupporting
confidence: 59%
“…A retrospective analysis showed that, among 206 patients reactive for specific antibodies, 195 patients (95%) tested positive for ANAs. Within these cases, speckled and homogeneous were identified as the predominant ANA patterns [28]. A cross-sectional study among 495 SLE patients revealed that the most frequently observed ANA patterns were speckled (52.1%) and homogeneous (35.2%) patterns [29].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Menor Almagro et al reported 69.6% association of speckled pattern with SS-A/Ro 60, SS-A/Ro52, and anti-La [30], followed by homogenous pattern (N=167) which was associated with dsDNA135 (80.8%), nucleosome 110 (65.9%), and histones 42 (25.1%). Again, Anis et al reported that speckled and homogenous were the predominant ANA patterns (56% and 42%, respectively) and they were associated with Sm/RNP, histones, and nucleosomes antibodies [12].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported positive autoantibodies by different methods in ANA-IIF assay-negative SLE. In a study by Enis et al, 5% of his patients was negative for ANA-IIF assay and positive for at least one antibody by immunoblot assay [12]. Another study by Gualtierotti reported that 7.4% of their SLE patients were ANA-IIF negative at the beginning of follow-up [13].…”
Section: Introductionmentioning
confidence: 93%